Perilipin 5 Reduces Oxidative Damage Associated With Lipotoxicity by Activating the PI3K/ERK-Mediated Nrf2-ARE Signaling Pathway in INS-1 Pancreatic β-Cells - Zhu, Yunxia; Ren, Chenxi; Zhang, Mingliang; Zhong, Yuan (Frontiers in Endocrinology, 2020)
Oxidative stress induced by free fatty acid overload in pancreatic β-cells is a potential contributory factor to dysfunction of insulin secretion and apoptotic cell death. Perilipin 5 (Plin5) has been reported to ameliorate oxidative stress-mediated damage in non-insulin-secreting tissues. We tested the hypothesis that Plin5 plays a similar role in pancreatic β-cells, which are extremely sensitive to oxidative stress. Here, our in vitro data showed that Plin5-mediated alleviation of palmitate-triggered apoptosis involves the mitochondrial pathway. And the protective role of Plin5 on β-cells was partially dependent on its modulation in oxidative stress. Upregulation of Plin5 in INS-1 cells decreased reactive oxygen species production, enhanced cellular glutathione levels and induced expression of antioxidant enzymes glutamate-cysteine ligase catalytic subunit and heme oxygenase-1. However, knocking out of Plin5 abolished all of these beneficial effects. Furthermore, by using the O2− scavenger MnTMPyP, we verified that altering Plin5 expression impacted lipotoxic cell death partially via modulating oxidative stress. Mechanistic experiments revealed that Plin5 induced Nrf2-ARE system, a master regulator in the cellular adaptive response to oxidative stress, by activating PI3K/Akt and ERK signal pathways, contributing to the increase of antioxidant defense and consequently improving β-cell function and survival in the presence of lipotoxic oxidative stress. Overall, our findings indicate that Plin5 abrogates oxidative damage in INS-1 β-cells during lipotoxic stress partially through the enhancement of antioxidant defense involving the PI3K/Akt and ERK mediated Nrf2-ARE system.